2011
DOI: 10.1002/hep.24108
|View full text |Cite
|
Sign up to set email alerts
|

Matrix stiffness modulates proliferation, chemotherapeutic response, and dormancy in hepatocellular carcinoma cells

Abstract: There is increasing evidence that the physical environment is a critical mediator of tumor behavior. Hepatocellular carcinoma (HCC) develops within an altered biomechanical environment, and increasing matrix stiffness is a strong predictor of HCC development. The aim of this study was to establish whether changes in matrix stiffness, which are characteristic of inflammation and fibrosis, regulate HCC cell proliferation and chemotherapeutic response. Using an in vitro system of “mechanically tunable” matrix‐coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
512
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 572 publications
(557 citation statements)
references
References 36 publications
21
512
2
2
Order By: Relevance
“…Besides influencing cellular behavior based on specific molecular signaling, dimensionality and biomechanical cues in the lung clearly impact the effect of ECM on interstitial cell phenotype (8)(9)(10)(11)(12)(13)(14)(15). Although traditional in vitro studies of cell-matrix interactions usually rely on matrix-coated culture dishes, these artificial environments do not truly recapitulate the in vivo conditions under which cells reside.…”
mentioning
confidence: 99%
“…Besides influencing cellular behavior based on specific molecular signaling, dimensionality and biomechanical cues in the lung clearly impact the effect of ECM on interstitial cell phenotype (8)(9)(10)(11)(12)(13)(14)(15). Although traditional in vitro studies of cell-matrix interactions usually rely on matrix-coated culture dishes, these artificial environments do not truly recapitulate the in vivo conditions under which cells reside.…”
mentioning
confidence: 99%
“…[83][84][85][86] Numerous studies have proven that stiffer substrates enhance the metastatic phenotypes of cancer cells. [87][88][89][90][91] However, within the field of ovarian cancer, studies have resulted in contradictory findings.…”
Section: Ecm Stiffness Within the Ovarian Cancer Mechanical Microementioning
confidence: 99%
“…Recent studies have suggested an important role for mechanical factors in the induction and maintenance of tumor cell dormancy. Schrader et al 6 showed that a soft physiological environment (eg, that encountered in the bone marrow niche) induces HCC cell dormancy, whereas increased matrix stiffness may be responsible for the reactivation of dormant tumor cells. This would explain the increased frequency of HCC recurrence in fibrotic allografts and may help to explain the very late recurrence seen in this patient after a long evolution of chronic HCV in the allograft resulted in increased fibrosis.…”
Section: To the Editorsmentioning
confidence: 99%
“…This would explain the increased frequency of HCC recurrence in fibrotic allografts and may help to explain the very late recurrence seen in this patient after a long evolution of chronic HCV in the allograft resulted in increased fibrosis. The process of reactivation from dormancy, which may involve the mesenchymal-to-epithelial transition, after the epithelial-tomesenchymal transition undergone by the malignant cells to enter the dormancy state 6 could explain the loss of HepPar1 staining in the recurrent HCC. Welldifferentiated HCCs are almost universally positive for HepPar1, but this hepatocytic differentiation marker has, to our knowledge, not been studied in the context of intrahepatic recurrences of HCCs.…”
Section: To the Editorsmentioning
confidence: 99%